SYNTHESIS AND CHARACTERIZATION BaFe (12-xTi0.5xMg0.5xO19 AND VARIATION (x = 0.5;1;1.5;2) WITH DOPING Ti-Mg THROUGH POWDER METALLURGY METHOD FOR ELECTROMAGNETIC WAVE ABSORBENT MATERIALS (RAMs) - Mulyati Latifah, Sri
The electromagnetic wave absorbent materials using the M-type ferrite BaFe(12-x) Ti0.5xMg0.5xO19 doped with Ti-Mg and variation of x=0.5;1;1,5;2 is synthesized by powder metallurgy method through pulverizing process 2,4 and 8 hours. The aim of this research work is to make electromagnetic wave absorbing materials (RAMs = Radar Absorbent Materials) and to understand the effect of doping addition of Ti-Mg elements on increasing magnetic properties of barium hexaferrite also to unerstand the result of pulverizing process to the absorption value of electromagnetic wave. From the result XRD test doping additions can change the latice parameter a, b, c on the hexagonal crystalline system, where the crystal volume increases then the X-Ray density will decrease. The XRD results can be confirmed by SEM test results with the formation hexagonal crystal structure on a pelletized sample with 5000x magnification. While the powdered sample showed a rough size change taken with the smallest average value detected with SEM was 217.63 nm after pulverizing process for 8 hours, and looked agglomerated powder. From the results of research on BaFe(12- x)Ti0.5xMg0.5xO19 with the addition of doping can improve the magnetic properties and absorption values of electromagnetic waves. The more addition of doping Ti- Mg for x=2 its magnetic properties is increasing with coercivity value of 0.177 kOe, saturation magnetization, Ms 54.013 emu/gram and remanent magnetization, Mr 21.744 emu/gram. For the highest electromagnetic wave absorption value or reflection loss is achieved at x=1.5 with thickness of 2 mm equal to -19.500 dB at frequency 10.300 GHz.